A magnetic resin-supported ionic liquid heteropolyacid catalyst and its preparation method and application

By using magnetic resin solid-supported ionic liquid heteropolyacid catalysts in benzyl alcohol oxidation reaction, and synthesizing magnetic phenolic resin microspheres in combination with ultrasonic-microwave technology, the existing catalyst pollution, low utilization rate and difficulty in recycling are solved, and efficient and low-cost catalyst application and recycling are achieved.

CN119318997BActive Publication Date: 2025-04-01ZHEJIANG XIANFENG TECHNOLOGIES CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411876829.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-01
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The existing catalysts have problems such as heavy metal contamination, low oxidant utilization, difficulty in separation and recycling in benzyl alcohol oxidation reaction, and the cost of precious metal catalysts is high, which limits their large-scale application.

Method used

Magnetic resin solid-carrying ionic liquid heteropolyacid catalyst is used to synthesize magnetic phenolic resin microspheres through ultrasonic-microwave technology, and the heteropolyacid is solid-carrying on its surface, so as to achieve simple recovery of the catalyst by using ferromagnetic properties.

Benefits of technology

The high catalytic activity of heteropoly acids is maintained, and the problems of easy loss of catalysts and difficult separation are solved, the amount of catalysts used and synthesis cost are reduced, and the efficient recovery of catalysts is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318997B_ABST
    Figure CN119318997B_ABST
Patent Text Reader

Abstract

The invention discloses a magnetic resin-supported ionic liquid heteropolyacid catalyst and its preparation method and application. Nano Fe3O4, polyformaldehyde and 3-hydroxy-N, N-dimethylaniline are mixed in an organic solvent for reaction, and magnetic resin microspheres are obtained after washing, drying and curing; the obtained magnetic resin microspheres are sequentially reacted with 1,3-propane sultone and heteropolyacid to obtain a magnetic resin-supported ionic liquid heteropolyacid catalyst; alcohol and hydrogen peroxide are used as raw materials, the magnetic resin-supported ionic liquid heteropolyacid is used as a catalyst, and the reaction is carried out in a 70-110°C oil bath for 0.5-4h; the reaction is cooled after completion, the catalyst is separated by an external magnetic field, the catalyst is washed with ether, dried and directly reused for the next reaction, and the product is obtained after recrystallization. The present invention solves the problems that the traditional heteropolyacid catalyst itself is easily soluble in polar solvents and difficult to separate during use, and the catalyst preparation time is long.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalyst preparation, and in particular relates to a magnetic resin-immobilized ionic liquid heteropolyacid catalyst and a preparation method and application thereof. Background Art

[0002] The oxidation of alcohols to ketones or aldehydes has important applications in pharmaceutical chemicals and the synthesis of flavors and fragrances. In the fragrance industry, aldehyde and ketone fragrances account for 25% of the total fragrances. Benzyl alcohol oxidation is widely used in the preparation of pharmaceutical intermediates and other fields. The selective oxidation of benzyl alcohol is an important step in the preparation of 1-(4-fluorophenyl)-2-acetophenone, an intermediate for atorvastatin-type lipid-lowering drugs.

[0003] Chromium-based oxidants are commonly used in the oxidation of benzyl alcohol to ketones or aldehydes, such as PDC (pyridinium dichromate) and PCC (pyridinium chlorochromate). They have high catalytic efficiency, but chromium itself is a heavy metal, which causes serious environmental pollution and does not meet the requirements of sustainable development. In addition, the atomic utilization rate of the oxidant is low and overoxidation is prone to occur in the reaction. In view of these problems, the development of new catalytic oxidation systems for selective catalytic oxidation has attracted much attention. Precious metal catalysts such as Ru, Pd and Pt have been reported in a large number of literatures for the selective oxidation of benzyl alcohol, but the high price of precious metal catalysts limits their large-scale application.

[0004] Heteropolyacids are a new type of oxidation reaction catalyst. Compared with other catalysts, they have good catalytic activity, so they no longer need to be combined with complex ligands. Heteropolyacids have a variety of unique structures such as Keggin structure, which gives them strong acidity, strong oxidizing properties and "pseudo-liquid phase" properties. Heteropolyacids are stable during the reaction process and can be used in a variety of different catalytic systems. However, the low specific surface area and easy solubility in polar solvents of heteropolyacids make it difficult to separate after the catalytic reaction, thus limiting their industrial application.

[0005] In recent years, ionic liquids have attracted widespread attention in many fields such as catalysis and extraction due to their designable structure and non-volatile properties. However, their high viscosity and high price limit their widespread application. The designable structural characteristics of ionic liquids enable them to act as ligands to combine with heteropolyacids to form ionic liquid heteropolyacids, and the inherent "self-separation" properties of heteropolyacids are used to improve their high viscosity and high cost. Despite this, ionic liquid heteropolyacids still have problems such as fine particles and easy loss of active ingredients. Immobilization of ionic liquid heteropolyacids can effectively solve these problems.

[0006] Resin microspheres represented by epoxy resin, polyvinyl chloride and phenolic resin have been widely reported in the fields of drug delivery and catalyst loading due to their modifiable structure. Phenolic resin is a type of polymer resin formed by condensation reaction of phenol or its homologues with aldehydes. As a material, it exhibits excellent physical and chemical properties. By regulating the pH of the polycondensation reaction, the synthesis of bulk (thermosetting) or linear (thermoplastic) phenolic resin can be controlled. Bulk phenolic resin can be controllably prepared into microspheres of different particle sizes by high-temperature thermal curing. By modifying the benzene ring and introducing different groups, the requirements for different functions and properties of phenolic resin can be met. Summary of the invention

[0007] The purpose of the present invention is to provide a magnetic resin-immobilized ionic liquid heteropolyacid catalyst, a preparation method thereof and an application thereof, which solves the problems of easy loss and difficult separation of heteropolyacid and ionic liquid heteropolyacid catalyst during use while maintaining the high catalytic alcohol oxidation activity of the ionic liquid heteropolyacid through the combined effect of chemical bonds, the larger particle size of resin microspheres and ferromagnetism.

[0008] A method for preparing a magnetic resin-immobilized ionic liquid heteropolyacid catalyst comprises:

[0009] (1) Nano-Fe3O4 and polyformaldehyde are added to an organic solvent. After ultrasonic treatment, a certain amount of 3-hydroxy-N,N-dimethylaniline is added dropwise to the solution under stirring conditions and microwave heating-assisted synthesis is performed. After the reaction is completed, the organic solvent and formaldehyde are evaporated under reduced pressure, washed with ethanol, filtered, and vacuum dried to obtain a magnetic resin.

[0010] (2) The magnetic resin is dissolved in a certain amount of alcohol solution, and after ultrasonic dispersion, dimethyl silicone oil is added to the dispersion, and the mixture is fully stirred, solidified, washed, and dried to obtain magnetic resin microspheres.

[0011] (3) The obtained magnetic resin microspheres are reacted with 1, 3-propane sultone and heteropoly acid in sequence, and then concentrated, washed and dried to obtain a magnetic resin-immobilized ionic liquid heteropoly acid catalyst.

[0012] In step (1): Optionally, the 3-hydroxy-N,N-dimethylaniline, paraformaldehyde and nano-Fe3O4 are commercially available products.

[0013] Optionally, the organic solvent is triethylamine or tripropylamine or DMF.

[0014] The catalyst preparation route is as follows:

[0015]

[0016] Optionally, the molar ratio of the 3-hydroxy-N,N-dimethylaniline to the polyformaldehyde (calculated as formaldehyde monomer) is 1:1.5-3.

[0017] Preferably, the molar ratio of the 3-hydroxy-N,N-dimethylaniline to paraformaldehyde (calculated as formaldehyde monomer) is 1:2.

[0018] Optionally, the mass ratio of nano-Fe3O4 to the volume of the organic solvent is 5-10 g:100 mL.

[0019] Optionally, in step (2): the volume of the alcohol solution is 1-4 times the mass of the magnetic resin, the volume unit is mL, and the mass unit is g, so that it is fully dissolved, and then added to methyl silicone oil to fully shape and solidify to obtain magnetic resin microspheres.

[0020] Optionally, in step (3): the mixing ratio of the magnetic resin microspheres and 1,3-propane sultone is 1-6 mmol:1g, and the solvent used is acetonitrile.

[0021] In step (3), the ratio of the heteropoly acid to the magnetic resin microspheres is 1-5 mmol:1 g.

[0022] Optionally, the heteropolyacid is phosphotungstic acid.

[0023] Optionally, the reactions of step (1) and step (3) are both carried out in an ultrasonic synthesizer.

[0024] Optionally, in step (1), the reaction temperature is 50-70° C., the ultrasonic power is 200-400 W, the microwave power is 100-400 W, and the reaction time is 0.5-1 h.

[0025] Optionally, in step (3), the 1,3-propane sultone modification reaction temperature is 50-80°C, the ultrasonic power is 200-600W, the microwave power is 100-400W, and the reaction time is 2-4 h; in step (3), the heteropolyacid modification reaction temperature is 50-100°C, and the reaction time is 6-24 h.

[0026] Preferably, in step (1), the reaction temperature is 60°C, the ultrasonic power is 300 W, the microwave power is 250 W, and the reaction time is 0.75 h; in step (3), the 1,3-propane sultone modification reaction temperature is 60°C, the ultrasonic power is 400 W, the microwave power is 250 W, and the reaction time is 3 h; in step (3), the heteropolyacid modification reaction temperature is 80°C, and the reaction time is 12 h.

[0027] A magnetic resin-supported ionic liquid heteropolyacid catalyst prepared by the preparation method.

[0028] Specifically, the magnetic resin-immobilized ionic liquid phosphotungstic acid (Fe3O4@PR-SO3-PW) catalyst has the structural formula shown below:

[0029]

[0030] The present invention also provides an application of a magnetic resin-immobilized ionic liquid heteropolyacid catalyst in the preparation of 1-(4-fluorophenyl)-2-acetophenone, comprising:

[0031] 1-(4-fluorophenyl)-2-phenylethanol and 30% H2O2 are used as raw materials and magnetic resin-immobilized ionic liquid heteropoly acid is used as catalyst to react in a solvent; after the reaction, the catalyst is separated by an external magnetic field; the solvent is evaporated and concentrated to obtain a crude 1-(4-fluorophenyl)-2-acetophenone, and then the refined 1-(4-fluorophenyl)-2-acetophenone is obtained by recrystallization.

[0032] The reaction route is as follows:

[0033]

[0034] Several optional methods are also provided below, but they are not intended to be additional limitations on the above-mentioned overall solution, but are merely further supplements or preferences. Under the premise that there are no technical or logical contradictions, each optional method can be combined with the above-mentioned overall solution separately, and multiple optional methods can also be combined.

[0035] Optionally, the molar ratio of 1-(4-fluorophenyl)-2-phenylethanol to 30% H2O2 is 1:1-4; further optionally 1:2.

[0036] Optionally, the amount of the catalyst used is 2-6% of the mass of 1-(4-fluorophenyl)-2-phenylethanol; further optionally 4%.

[0037] Optionally, the reaction temperature is 70-110°C; further optionally 90°C.

[0038] Optionally, the reaction time is 0.5 to 4 h; further optionally 2 h.

[0039] Optionally, the solvent is one of acetonitrile, water, and a mixture of acetonitrile and water.

[0040] Optionally, after the reaction is completed, the mixture is cooled and the catalyst is recovered by an external magnetic field. The catalyst is washed with ether, dried and directly reused in the next reaction.

[0041] The stability, high cost and difficulty of separation of catalysts have always been the problems faced by heteropolyacid catalysts. With magnetic materials as the center, the bulk magnetic resin is synthesized by regulating the pH value, and the magnetic phenolic resin microspheres are prepared by further controlling the conditions; then, the ionic liquid heteropolyacid is combined with the ionic liquid heteropolyacid through chemical bonds in turn, and finally the magnetic resin-immobilized ionic liquid heteropolyacid is formed. Through the action of chemical bonds, the loss of active components is reduced. Using organic base as the alkali source in the reaction system can catalyze the polycondensation of phenolic resin and the synthesis of thermosetting phenolic resin. Alkaline conditions are conducive to reducing side reactions and depolymerizing polyformaldehyde, thereby reducing the harm of formaldehyde use to operators. In addition, through ultrasonic-microwave technology, the degradation of polyformaldehyde and the polycondensation of phenolic resin are greatly promoted, while the catalyst preparation time is shortened, and the energy consumption and cost are reduced. The ionic liquid heteropolyacid is widely dispersed on the surface of the microspheres, increasing the reaction active sites, thereby reducing the use of ionic liquid heteropolyacids and reducing the synthesis cost. After the reaction, the catalyst separation can be easily achieved through an external magnetic field. Therefore, the ultrasonic-microwave preparation and catalytic oxidation performance research of magnetic resin-immobilized ionic liquid heteropolyacid catalysts has good application prospects.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] (1) The present invention uses paraformaldehyde, 3-hydroxy-N,N-dimethylaniline and nano-Fe3O4 as raw materials, forms magnetic 3-hydroxy-N,N-dimethylaniline aldehyde resin under the catalysis of organic base, and forms microspheres through dispersion and thermal curing. The safe paraformaldehyde is used as the raw material, providing a method for synthesizing magnetic phenolic resin microspheres with high efficiency, safety and low cost;

[0044] (2) The present invention uses homemade magnetic phenolic resin microspheres, 1,3-propane sultone, and heteropoly acid as raw materials to prepare a magnetic resin-immobilized ionic liquid heteropoly acid catalyst, which retains the catalytic activity of the heteropoly acid. At the same time, the heteropoly acid is fixed by a carrier, which reduces the problem of dissolution in polar solvents and reduces the amount of catalyst used; the preparation process is simple and the preparation cost is low;

[0045] (3) The present invention solves the problem that heteropolyacid catalysts are difficult to recycle. When the heteropolyacid catalyst is modified by homemade ionic liquid magnetic phenolic resin microspheres, the particles are large and magnetic, and can be reused by simple magnetic attraction, filtration and washing.

[0046] (4) The present invention immobilizes the heteropoly acid and disperses it on the surface of the microspheres, thereby dispersing the active centers, improving the catalytic activity, and reducing the amount of heteropoly acid used;

[0047] (5) The present invention solves the problems of harsh reaction conditions, environmental pollution and complicated post-treatment of commonly used benzyl alcohol oxidation catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is the infrared spectrum of the magnetic resin-immobilized ionic liquid phosphotungstic acid catalyst in Example 1.

[0049] Figure 2 This is a graph showing the reusability performance results of the magnetic resin-immobilized ionic liquid phosphotungstic acid catalyst in Example 7. DETAILED DESCRIPTION

[0050] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0051] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0052] The catalyst prepared in this application adopts ultrasonic microwave assisted solvothermal method, and the catalyst preparation process has the advantages of rapid, efficient, green and controllable, and low cost. After the reaction is completed, the catalyst is easy to separate from the reaction system and has great application potential. Specifically, the following steps are included:

[0053] (1) Add nano-Fe3O4 and polyformaldehyde to an organic solvent, and after ultrasonic treatment, add a certain amount of 3-hydroxy-N,N-dimethylaniline to the solution under stirring conditions and perform microwave heating-assisted synthesis; after the reaction is completed, evaporate the organic solvent and formaldehyde under reduced pressure, wash with ethanol, filter, and vacuum dry to obtain a magnetic resin. The reaction temperature in the steps is 50-70°C, the ultrasonic power is 200-400W, the microwave power is 100-400W, and the time is 0.5-1h.

[0054] (2) The magnetic resin is dissolved in a certain amount of alcohol solution, and after ultrasonic dispersion, dimethyl silicone oil is added to the dispersion, and the mixture is fully stirred, solidified, washed, and dried to obtain magnetic resin microspheres.

[0055] (3) The obtained magnetic resin microspheres are reacted with 1,3-propane sultone and heteropoly acid in sequence, and then concentrated, washed and dried to obtain a magnetic resin-immobilized ionic liquid heteropoly acid catalyst. In the step, the reaction temperature with 1,3-propane sultone is 50-80 ° C, the ultrasonic power is 200-600 W, the microwave power is 100-400 W, and the time is 2-4 h. In the step, the reaction temperature with heteropoly acid is 50-100 ° C, and the reaction time is 6-24 h.

[0056] The preparation method of the magnetic resin-immobilized ionic liquid heteropolyacid catalyst is described below with specific examples:

[0057] The raw materials used in the following examples are all commercially available products.

[0058] Example 1

[0059] This example takes the preparation of a magnetic resin-immobilized ionic liquid heteropolyacid catalyst as an example, and the preparation method of the catalyst is as follows:

[0060] (1) 5 g of nano-Fe3O4 and 3 g of paraformaldehyde were mixed in 100 mL of triethylamine and thoroughly ultrasonically mixed to obtain a mixed solution; 6.8 g of 3-hydroxy-N,N-dimethylaniline was added to the obtained mixed solution, and the mixture was reacted at 60°C, an ultrasonic power of 300 W, and a microwave power of 250 W for 45 min; triethylamine and excess formaldehyde were removed by reduced pressure evaporation, and the mixture was washed with ethanol several times, filtered, and vacuum dried to obtain a magnetic resin.

[0061] (2) The obtained magnetic resin was dissolved in 35 mL of ethanol solution, and then dispersed in dimethyl silicone oil, stirred thoroughly, cured at 110° C. for 1 h, washed, and dried to obtain magnetic resin microspheres.

[0062] (3) Dissolve 3 mmol 1,3-propanesulfonate in acetonitrile, add 1 g magnetic 3-hydroxy-N,N-dimethylaniline resin microspheres, stir at 70 °C for 3 h with ultrasonic power of 400 W and microwave power of 250 W, and then wash with ethyl acetate; mix the above substances with 2 mmol phosphotungstic acid in distilled water, stir at 90 °C for 12 h, terminate the reaction, cool, concentrate to obtain a solid, wash with ether several times, and vacuum dry to obtain a magnetic resin-supported ionic liquid heteropolyacid catalyst Fe3O4@PR-SO3-PW. The infrared spectrum of the obtained catalyst is shown in Figure 1 , (a) in the figure represents H3PW 12 O 40 , (b) represents Fe3O4, (c) represents Fe3O4@PR-SO3-PW. It can be seen from the figure that the heteropoly acid is successfully immobilized on the carrier and the stable structure of the heteropoly acid is maintained.

[0063] Based on the catalyst prepared in Example 1 above, a method for catalyzing the oxidation of alcohol to ketone (aldehyde) using a magnetic resin-immobilized ionic liquid heteropolyacid catalyst is proposed, comprising the following steps:

[0064] (1) 1-(4-fluorophenyl)-2-phenylethanol and 30% H2O2 are used as raw materials, and the magnetic resin-immobilized ionic liquid heteropoly acid is used as a catalyst, dispersed in a solvent, and reacted in an oil bath;

[0065] (2) After the reaction is completed, the reaction mixture is cooled and the catalyst is separated by applying an external magnetic field. The catalyst can be directly reused in the next catalysis after being washed with ether and dried.

[0066] (3) The organic phase was quantitatively analyzed on an Agilent 7890B gas chromatograph (FID detector, HP-5 capillary column), with biphenyl as the internal standard, and the conversion rate and yield of the reactants were calculated. The solvent was then evaporated and concentrated to obtain the crude 1-(4-fluorophenyl)-2-acetophenone, which was then recrystallized to obtain the refined 1-(4-fluorophenyl)-2-acetophenone.

[0067] It should be noted that the molar ratio of 1-(4-fluorophenyl)-2-phenylethanol to 30% H2O2 is 1:1-4; the reaction temperature is 70-110°C; the reaction time is 0.5-4h; the solvent is acetonitrile, water or a mixture of acetonitrile and water; the amount of the catalyst is 2-6% of the mass of 1-(4-fluorophenyl)-2-phenylethanol.

[0068] The following is a specific application example:

[0069] The raw materials used in the following examples are all commercially available products.

[0070] Example 2

[0071] In order to verify the catalytic effect of the catalyst prepared by different ultrasonic powers, this example explored the catalytic effect of the ultrasonic power on the catalyst in step (3) of Example 1. The other conditions were fixed and the ultrasonic power was changed to react with 1,3-propane sultone. According to the conditions of Example 1, the reaction with phosphotungstic acid and the catalytic alcohol oxidation reaction were carried out. The operation process of catalytic alcohol oxidation was to add 40 mL of acetonitrile, 20 mL of water, 10.8 g of 1-(4-fluorophenyl)-2-phenylethanol, and 0.432 g of catalyst (prepared by different ultrasonic powers) to a 100 mL three-necked flask equipped with a constant pressure dropping funnel. 11.58 g of 30% H2O2 was placed in the constant pressure dropping funnel, and it was placed in a 90°C oil bath for heating reaction. The H2O2 was dripped in 10 minutes, and the reaction was carried out for 2 hours. The yield and conversion rate of the reaction product were analyzed by gas chromatography. The microwave power was fixed at 250 W, and the results of the oxidation reaction of 1-(4-fluorophenyl)-2-phenylethanol catalyzed by the obtained catalysts under different ultrasonic powers are shown in Table 1. It can be seen from the table that the yield of the target product is the highest when the catalyst is treated with an ultrasonic power of 400 W. From the perspective of energy saving, the ultrasonic power is determined to be 400 W.

[0072] Table 1 Results of alcohol oxidation catalyzed by catalysts prepared with different ultrasonic powers

[0073]

[0074] Example 3

[0075] To verify the catalytic effect of catalysts with different reaction times, in this example, 40 mL of acetonitrile, 20 mL of water, 10.8 g of 1-(4-fluorophenyl)-2-phenylethanol, and 0.432 g of catalyst (prepared in Example 1) were added to a 100 mL three-necked flask equipped with a constant pressure dropping funnel. 11.58 g of 30% H2O2 was loaded into the constant pressure dropping funnel, and it was placed in a 90 ° C oil bath for heating reaction. H2O2 was dripped within 10 minutes. The reaction was carried out for 0.5-4 h respectively, and the yield and conversion rate of the reaction product were analyzed by gas chromatography. The reaction results of 1-(4-fluorophenyl)-2-phenylacetophenone obtained by changing the reaction time are shown in Table 2. Considering the comprehensive reaction efficiency and the yield of the target product, the optimal reaction time was determined to be 2 h.

[0076] Table 2 Reaction results of 1-(4-fluorophenyl)-2-acetophenone obtained at different reaction times

[0077]

[0078] Example 4

[0079] To a 100mL three-necked flask equipped with a constant pressure dropping funnel, 40mL of acetonitrile, 20mL of water, 10.8g of 1-(4-fluorophenyl)-2-phenylethanol, and 0.432g of catalyst (prepared in Example 1) were added in sequence, and 30% H2O2 was placed in a 90°C oil bath for heating reaction. H2O2 was dripped within 10min. The reaction was terminated after 2 h of reaction, and the yield and conversion rate of the reaction product were analyzed by gas chromatography. The reaction results of 1-(4-fluorophenyl)-2-phenylacetophenone obtained by changing the molar ratio of alcohol to H2O2 are shown in Table 3. From the perspective of resource conservation and target product yield, the optimal molar ratio of alcohol to H2O2 was determined to be 1:2.

[0080] Table 3 Reaction results of 1-(4-fluorophenyl)-2-acetophenone obtained with different molar ratios of H2O2

[0081]

[0082] Example 5

[0083] To a 100mL three-necked flask equipped with a constant pressure dropping funnel, 40mL of acetonitrile, 20mL of water, 10.8g of 1-(4-fluorophenyl)-2-phenylethanol, and a catalyst (prepared in Example 1) were added in sequence. 11.58g of 30% H2O2 was placed in a constant pressure dropping funnel and heated in a 90°C oil bath for reaction. H2O2 was dripped in 10 min. The reaction was terminated after 2 h of reaction, and the yield and conversion rate of the reaction product were analyzed by gas chromatography. The reaction results of 1-(4-fluorophenyl)-2-phenylacetophenone obtained by changing the amount of catalyst are shown in Table 4. From the perspective of resource conservation and target product yield, the optimal catalyst dosage was determined to be 4% (the catalyst was 4% of the mass of 1-(4-fluorophenyl)-2-phenylethanol).

[0084] Table 4 Reaction results of 1-(4-fluorophenyl)-2-acetophenone obtained by different amounts of catalyst

[0085]

[0086] Example 6

[0087] To a 100mL three-necked flask equipped with a constant pressure dropping funnel, 40 mL of acetonitrile, 20 mL of water, 10.8 g of 1-(4-fluorophenyl)-2-phenylethanol, and 0.432 g of catalyst (prepared in Example 1) were added in sequence, and 11.58 g of 30% H2O2 was placed in the constant pressure dropping funnel, which was placed in an oil bath for heating reaction, and H2O2 was dripped within 10 min. The reaction was terminated after 2 h of reaction, and the yield and conversion rate of the reaction product were analyzed by gas chromatography. The reaction results of 1-(4-fluorophenyl)-2-phenylacetophenone obtained by changing the reaction temperature are shown in Table 5. From the perspective of energy saving and target product yield, the optimal reaction temperature was determined to be 90°C.

[0088] Table 5 Reaction results of 1-(4-fluorophenyl)-2-acetophenone obtained at different reaction temperatures

[0089]

[0090] Example 7

[0091] After the reaction in the above embodiment is completed, the reaction is cooled and the catalyst is separated by using an external magnetic field. After separation, the catalyst is washed with ether and dried to obtain a recovered catalyst.

[0092] To a 100mL three-necked flask equipped with a constant pressure dropping funnel, 40 mL of acetonitrile, 20 mL of water, 10.8 g of 1-(4-fluorophenyl)-2-phenylethanol, and 0.432 g of catalyst (prepared in Example 1) were added in sequence. 11.58 g of 30% H2O2 was placed in the constant pressure dropping funnel and heated in a 90°C oil bath for reaction. H2O2 was dripped in 10 min. The reaction was terminated after 2 h of reaction, and the yield and conversion rate of the reaction product were analyzed by gas chromatography. The reusability of the magnetic resin-immobilized ionic liquid heteropolyacid catalyst for the oxidation reaction of 1-(4-fluorophenyl)-2-phenylethanol is as follows: Figure 2 As shown in the figure, it can be seen that in the presence of H2O2, the catalyst has good stability and reusability when catalyzing the oxidation reaction of 1-(4-fluorophenyl)-2-phenylethanol.

[0093] Comparative Example 1

[0094] To a 100mL three-necked flask equipped with a constant pressure dropping funnel, 40 mL of acetonitrile, 20 mL of water, 10.8 g of 1-(4-fluorophenyl)-2-phenylethanol, 0.432 g of different catalysts were selected, 11.58 g of 30% H2O2 was loaded into the constant pressure dropping funnel, and it was placed in a 90℃ oil bath for heating reaction. H2O2 was dripped within 10 min. The reaction was completed after 2 h of reaction, and the yield and conversion rate of the reaction product were analyzed by gas chromatography. The reaction results of 1-(4-fluorophenyl)-2-phenylacetaldehyde obtained by changing different catalysts are shown in Table 6. As can be seen from Table 6, the magnetic resin-immobilized ionic liquid heteropolyacid catalyst has the best target product yield under the reaction conditions.

[0095] Table 6 Reaction results of 1-(4-fluorophenyl)-2-phenylacetaldehyde obtained by different catalysts

[0096]

[0097] Comparative Example 2

[0098] To a 100mL three-necked flask equipped with a constant pressure dropping funnel, 40mL of acetonitrile, 20mL of water, and 10.8g of 1-(4-fluorophenyl)-2-phenylethanol were added in sequence. Ammonium tungstate was used as a catalyst, and 0.432g of the catalyst was taken. 11.58g of 30% H2O2 was loaded into the constant pressure dropping funnel, and it was placed in a 90℃ oil bath for heating reaction. H2O2 was dripped in 10 minutes. The reaction was terminated after 2 hours of reaction, and the yield and conversion rate of the reaction product were analyzed by gas chromatography.

[0099] In addition, referring to the operating conditions described in Example 1 of patent CN201710264768.3, ammonium tungstate was used as a catalyst to carry out catalytic oxidation of 1-(4-fluorophenyl)-2-phenylethanol, and the reaction product was analyzed by gas chromatography for its yield and conversion rate. The reaction results of 1-(4-fluorophenyl)-2-phenylacetaldehyde obtained by changing different catalysts and conditions are shown in Table 7. As can be seen from Table 7, the magnetic resin-immobilized ionic liquid heteropolyacid catalyst has the best target product yield under the reaction conditions.

[0100] Table 7 Reaction results of 1-(4-fluorophenyl)-2-phenylacetaldehyde obtained by different catalysts and catalytic conditions

[0101]

[0102] Comparative Example 3

[0103] Reference patent CN201210185251.2 Example 1 Preparation method of catalyst to prepare AM-DVB-PW; to a 100mL three-necked flask equipped with a constant pressure dropping funnel, add 40 mL of acetonitrile, 20 mL of water, 10.8 g of 1-(4-fluorophenyl)-2-phenylethanol in sequence, take 0.432 g of AM-DVB-PW catalyst, load 11.58 g of 30% H2O2 into the constant pressure dropping funnel, place it in a 90℃ oil bath for heating reaction, and H2O2 drips within 10 min. The reaction is terminated after 2 h, and the reaction product is analyzed by gas chromatography for its yield and conversion rate.

[0104] In addition, referring to the catalytic conditions described in Example 1 of patent CN201210185251.2, AM-DVB-PW was used as a catalyst to carry out catalytic oxidation of 1-(4-fluorophenyl)-2-phenylethanol, and the yield and conversion rate of the reaction product were analyzed by gas chromatography. The reaction results of 1-(4-fluorophenyl)-2-phenylacetaldehyde obtained by changing different catalysts and conditions are shown in Table 8. As can be seen from Table 8, the magnetic resin-immobilized ionic liquid heteropolyacid catalyst has the best target product yield under the reaction conditions.

[0105] Table 8 Reaction results of 1-(4-fluorophenyl)-2-phenylacetaldehyde obtained under different catalysts and operating conditions

[0106]

[0107] Comparative Example 4

[0108] Preparation method of the catalyst of Example 1 of reference patent CN201911043552.X Preparation of binuclear ionic liquid type heteropolyacid salt solid acid catalyst [THDAPS] 1.5PW; Reference paper (Green Processing and Synthesis, 2017, 65(4): 385-395) Preparation of ionic liquid-based heteropolyacid catalyst. To a 100 mL three-necked flask equipped with a constant pressure dropping funnel, 40 mL of acetonitrile, 20 mL of water, and 10.8 g of 1-(4-fluorophenyl)-2-phenylethanol were added in sequence, 0.432 g of catalyst was taken, 11.58 g of 30% H2O2 was loaded into the constant pressure dropping funnel, and the funnel was placed in a 90 °C oil bath for heating reaction. H2O2 was dripped within 10 min. The reaction was completed after 2 h of reaction, and the yield and conversion rate of the reaction product were analyzed by gas chromatography. The reaction results of 1-(4-fluorophenyl)-2-phenylacetaldehyde obtained by changing different catalysts and conditions are shown in Table 9. As can be seen from Table 9, the magnetic resin-immobilized ionic liquid heteropolyacid catalyst has the best target product yield under the reaction conditions.

[0109] Table 9: Reaction results of 1-(4-fluorophenyl)-2-phenylacetaldehyde obtained by different catalysts

[0110]

[0111] Comparative Example 5

[0112] Reference patent CN202011454659.6 Sol-gel supported catalyst [QUPSH] 1H3Si-W 12 O 40 / SG-Fe3O4 (10%) preparation method to prepare this catalyst; reference paper "Solid-supported ionic liquid and its catalytic effect on the oxidation reaction of benzyl alcohol and styrene" SIL-FeCl3 type solid-supported ionic liquid catalyst preparation method to prepare SIL-FeCl3 type solid-supported ionic liquid catalyst; to a 100mL three-necked flask equipped with a constant pressure dropping funnel, add 40mL of acetonitrile, 20mL of water, 10.8g of 1-(4-fluorophenyl)-2-phenylethanol, take 0.432g of different catalysts, put 11.58g of 30%H2O2 in the constant pressure dropping funnel, place it in a 90℃ oil bath for heating reaction, and H2O2 drips within 10min. The reaction is completed after 2h, and the yield and conversion rate of the reaction product are analyzed by gas chromatography. The reaction results of 1-(4-fluorophenyl)-2-phenylacetaldehyde obtained by changing different catalysts are shown in Table 10. It can be seen from the table that the magnetic resin-immobilized ionic liquid heteropolyacid catalyst has the best target product yield under the reaction conditions.

[0113] Table 10 Reaction results of 1-(4-fluorophenyl)-2-phenylacetaldehyde obtained by different catalysts

[0114]

[0115] The above examples prove that this method can effectively reduce the amount of catalyst used, increase the number of times the catalyst is used, and is easy to recycle, and is a potential excellent catalyst for the oxidation of ketones / aldehydes by alcohols.

[0116] The present invention immobilizes the heteropoly acid on a magnetic ionic liquid carrier, thereby solving the problem of difficult recovery of the heteropoly acid, while retaining the catalytic activity of the heteropoly acid, and having low preparation cost. The process of synthesizing phenolic resin uses polyformaldehyde to provide formaldehyde, which reduces the damage to operators caused by the use of formaldehyde. In addition, the synthesis process introduces microwave-ultrasonic combined technology, which greatly reduces the preparation time of the catalyst, and reduces energy consumption and cost.

[0117] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. A method for preparing a magnetic resin-immobilized ionic liquid heteropolyacid catalyst, characterized in that: include: (1) Add nano-Fe3O4 and polyformaldehyde into an organic solvent, add 3-hydroxy-N,N-dimethylaniline dropwise into the solution under stirring conditions after ultrasonic treatment, and perform microwave heating-assisted synthesis. After the reaction is completed, remove the organic solvent and formaldehyde under reduced pressure, wash with ethanol, filter, and vacuum dry to obtain a magnetic resin; (2) dissolving the magnetic resin in an alcohol solution, ultrasonically dispersing the dispersion, adding the dispersion into dimethyl silicone oil, stirring thoroughly, solidifying, washing, and drying to obtain magnetic resin microspheres; (3) The obtained magnetic resin microspheres are reacted with 1, 3-propane sultone and heteropoly acid in sequence, and then concentrated, washed and dried to obtain a magnetic resin-immobilized ionic liquid heteropoly acid catalyst.

2. The method for preparing a magnetic resin-immobilized ionic liquid heteropolyacid catalyst according to claim 1, characterized in that: The organic solvent in step (1) is one of triethylamine, tripropylamine and DMF.

3. The method for preparing a magnetic resin-immobilized ionic liquid heteropolyacid catalyst according to claim 1, characterized in that: The molar ratio of 3-hydroxy-N,N-dimethylaniline to polyformaldehyde is 1:1.5~3 based on formaldehyde monomer; the mass ratio of nano-Fe3O4 to the volume of organic solvent is 5~10 g:100 mL.

4. The method for preparing a magnetic resin-immobilized ionic liquid heteropolyacid catalyst according to claim 1, characterized in that: In step (3), the mass ratio of the amount of 1,3-propane sultone to the mass ratio of the magnetic resin microspheres is 1-6 mmol:1 g, 1,3-propane sultone is dissolved in acetonitrile, and the magnetic resin microspheres are added for reaction; the mass ratio of the amount of heteropoly acid to the mass ratio of the magnetic resin microspheres is 1-5 mmol:1 g, wherein the heteropoly acid is phosphotungstic acid.

5. The method for preparing a magnetic resin-immobilized ionic liquid heteropolyacid catalyst according to claim 1, characterized in that: The reaction of step (1) and step (3) is carried out in a microwave-ultrasonic synthesizer; in step (1), the reaction temperature is 50-70°C, the ultrasonic power is 200-400W, the microwave power is 100-400W, and the reaction time is 0.5-1h; in step (3), the reaction temperature with 1,3-propane sultone is 50-80°C, the ultrasonic power is 200-600W, the microwave power is 100-400W, and the reaction time is 2-4h; in step (3), the reaction temperature with heteropoly acid is 50-100°C, and the reaction time is 6-24h; in step (2), the curing temperature is 100-130°C, and the curing time is 0.5-2h.

6. A magnetic resin-immobilized ionic liquid heteropolyacid catalyst prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the magnetic resin-supported ionic liquid heteropolyacid catalyst as claimed in claim 6 in the preparation of 1-(4-fluorophenyl)-2-acetophenone, characterized in that: include: 1-(4-fluorophenyl)-2-phenylethanol and 30% H2O2 are used as raw materials and magnetic resin-immobilized ionic liquid heteropoly acid is used as catalyst to react in a solvent; after the reaction, the catalyst is separated by an external magnetic field; the solvent is evaporated and concentrated to obtain a crude product of 1-(4-fluorophenyl)-2-acetophenone, and then the refined product of 1-(4-fluorophenyl)-2-acetophenone is obtained by recrystallization.

8. Use of the magnetic resin-supported ionic liquid heteropolyacid catalyst in the preparation of 1-(4-fluorophenyl)-2-acetophenone according to claim 7, characterized in that: The molar ratio of 1-(4-fluorophenyl)-2-phenylethanol to H2O2 is 1:1-4; the amount of the catalyst used is 2%-6% of the mass of 1-(4-fluorophenyl)-2-phenylethanol.

9. The use of the magnetic resin-supported ionic liquid heteropolyacid catalyst in the preparation of 1-(4-fluorophenyl)-2-acetophenone according to claim 7, characterized in that: The reaction temperature is 70-110° C.; the reaction time is 0.5-4 h, and the solvent used is one of acetonitrile, water, and a mixture of acetonitrile and water.

10. The use of the magnetic resin-immobilized ionic liquid heteropolyacid catalyst in the preparation of 1-(4-fluorophenyl)-2-acetophenone according to claim 7, characterized in that: After the reaction is completed, the catalyst is cooled and separated from the reaction system. The catalyst is recovered by an external magnetic field. The catalyst is washed with ether and dried and then directly reused in the next reaction.

Citation Information

Patent Citations

  • Method for preparing cyclohexanone from cyclohexanol under catalysis of ammonium tungstate

    CN108727178A

  • A binuclear ionic liquid heteropolyacid catalyst for the synthesis of chalcone derivatives, its preparation method and application.

    CN110732347B

  • A magnetic material-supported organic-inorganic hybrid catalyst, its preparation and application

    CN112570022B

  • Organic heteropoly acid hybrid catalyst for alcohol oxidation reaction and preparation method thereof

    CN102671700A

  • Immobilized heteropoly acid ionic liquid catalyst and preparation method thereof

    CN106732778A